Crinane, augustamine, and β-carboline alkaloids from Crinum latifolium. (April 2018) - Hanh, Tran Thi Hong; Anh, Do Hoang; Huong, Phan Thi Thanh; Thanh, Nguyen Van; Trung, Nguyen Quang; Cuong, Tran Van; Mai, Nguyen Thi; Cuong, Nguyen The; Cuong, Nguyen Xuan; Nam, Nguyen Hoai; Minh, Chau Van
Graphical abstract: Highlights: 9 Crinane, 1 augustamine, and 1 β -carboline alkaloids were isolated. Three new crinane-type alkaloids was elucidated by spectroscopic methods. This is the first report of N -oxide alkaloid from Crinum latifolium. Abstract: Three new crinane-type alkaloids, namely, 6-methoxyundulatine (1 ), 6-methoxycrinamidine (2 ), and undulatine N -oxide (3 ), along with the known compounds 6-hydroxyundulatine (4 ), 6-hydroxybuphanidrine (5 ), undulatine (6 ), crinamidine (7 ), ambelline (8 ), filifoline (9 ), augustamine (10 ), and perlolyrine (11 ), were isolated from the leaves of Crinum latifolium by using various chromatographic separations. Their structures were established by extensive analysis, including 1D and 2D NMR, HR-QTOF-MS, and CD data. Among the isolated compounds, perlolyrine (11 ) showed significant cytotoxicity against five human cancer cell lines, namely, KB, HepG2, MCF7, SK-Mel2, and LNCaP with the IC50 values ranging from 22.12 ± 2.80 to 28.45 ± 3.75 μM.